2020
DOI: 10.1002/mnfr.202000681
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Dietary Fish Oil Supplementation on the Recruitment of Brown and Brite Adipocytes in Mice or Humans under Thermoneutral Conditions

Abstract: Scope Brown and brite adipocytes within the mammalian adipose organ provide non‐shivering thermogenesis and thus, have an exceptional capacity to dissipate chemical energy as heat. Polyunsaturated fatty acids (PUFA) of the n3‐series, abundant in fish oil, have been repeatedly demonstrated to enhance the recruitment of thermogenic capacity in these cells, consequently affecting body adiposity and glucose tolerance. These effects are scrutinized in mice housed in a thermoneutral environment and in a human dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
(189 reference statements)
0
4
0
Order By: Relevance
“…It was noted that diets rich in ARA favor WAT formation by preventing the “browning” process 52 . However, recently published results suggest no effect of dietary fish oil supplementation on the recruitment of brown and brite adipocytes in mice or humans under thermoneutral conditions 53 . The thermoneutral conditions could be an explanation of noted conflicting results, since different circulating PUFA and oxylipins (being the lipid mediators produced from PUFA) profiles in BAT-positive and BAT-negative subjects were noted 54 and cold exposure significantly increased plasma lipid composition only in BAT-positive individuals, strongly supporting the relationship between BAT and PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that diets rich in ARA favor WAT formation by preventing the “browning” process 52 . However, recently published results suggest no effect of dietary fish oil supplementation on the recruitment of brown and brite adipocytes in mice or humans under thermoneutral conditions 53 . The thermoneutral conditions could be an explanation of noted conflicting results, since different circulating PUFA and oxylipins (being the lipid mediators produced from PUFA) profiles in BAT-positive and BAT-negative subjects were noted 54 and cold exposure significantly increased plasma lipid composition only in BAT-positive individuals, strongly supporting the relationship between BAT and PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study showed a similar antiobesity effect and stimulation of energy expenditure with fish oil supplementation in wild-type or UCP1 KO mice ( 734 ), suggesting that activation of BAT thermogenesis was not responsible for the effects of this treatment. Fish oil supplements in humans increased WAT browning in one report ( 735 ) but not in another ( 733 ). An association was reported between BAT 18 FDG uptake with fasting plasma DHA and EPA in humans ( 736 ).…”
Section: Pharmacological Activation Of Brown Adipose Tissuementioning
confidence: 84%
“…In contrast, treatment with ethyl EPA (icosapent ethyl) was shown to confer important cardiovascular benefits in high-risk participants in a large, randomized controlled trial ( 727 ). Despite some early reports of increased expression of iBAT UCP1 and thermogenic gene expression, increased BAT mass and induction of WAT browning with fish oil supplementation in rodents ( 728–732 ), a more recent report did not reproduce these findings under thermoneutral conditions ( 733 ). Another recent study showed a similar antiobesity effect and stimulation of energy expenditure with fish oil supplementation in wild-type or UCP1 KO mice ( 734 ), suggesting that activation of BAT thermogenesis was not responsible for the effects of this treatment.…”
Section: Pharmacological Activation Of Brown Adipose Tissuementioning
confidence: 90%
“…Human studies currently show that activation of thermogenic adipose tissue is associated with a small and negligible loss of fat mass [ 65 ] . Moreover, no dietary intervention has yet been shown to affect Ucp1 expression, which is only expressed at extremely low levels in subcutaneous fat depots [ 66 , 67 ] . Several authors demonstrated the effect of 5 mM metformin in the modulation of cell behaviour [ 68–70 ] , as well as of vitamin D, involved in osteogenic differentiation [ 34 , 71 ] .…”
Section: Discussionmentioning
confidence: 99%